Metabolic engineering of the moss Physcomitrella patens to produce the sesquiterpenoids patchoulol and α/β-santalene - Xin eZhan; Lei Arvin Han; Yu-Hua eZhang; Dong-Fang eChen; Henrik Toft Simonsen (Frontiers in Plant Science, 2014)
The moss Physcomitrella patens, has been genetically engineered to produce patchoulol and β-santalene, two valuable sesquiterpenoid ingredients in the fragrance industry. The highest yield of patchoulol achieved was 1.34 mg/g dry weight. This was achieved by non-targeted transformation of the patchoulol synthase and either a yeast or P. patens HMGR gene under the control of a 35S promoter. Santalene synthase targeted to the plastids yielded 0.039 mg/g dry weight of α/β santalene; cytosolic santalene synthase and 35S controlled HMGR afforded 0.022 mg/g dry weight. It has been observed that the final yield of the fragrance molecules is dependent on the expression of the synthase. This is the first report of heterologous production of sesquiterpenes in moss and it opens up a promising source for light-driven production of valuable fragrance ingredients.